Morphometrical studies on black pepper (Piper nigrum L.). II. principal component analysis of black pepper cultivars - BABU, P N RAVINDRAN, R BALAKRISHNAN, K NIRMAL (Journal of Spices and Aromatic Crops, 1997)
Forty four cultivars and seven wild accessions of black pepper (Piper nigrum) (51 Operational Taxonomic Units) were analysed adopting Principal Component Analysis to determine the nature and extent of divergence aniong them. Eight principal components emerged from the analysis and the dispersion pattern of Operational Taxonomic Units between the principal components (in principal component plots) showed the characters involved in the divergence of various cultivars. Dispersion of Operational Taxonomic Units between principal components showed that certain cultivars remain as independent entitles thereby indicating their divergence from other cultivars. The majority of cultivars are distributed around the central point, and this group is comparable to the group D obtained by the centroid clustering. Computation of inter and intracluster - D2 helped to establish further the extent of relationships among the clusters.